Post-Chemotherapy Secondary Brain Tumors in Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The longterm outcome of 198 infants with malignant brain tumors treated postoperatively with prolonged chemotherapy (vincristine, cyclophosphamide, cisplatinum, and etoposide) is evaluated by a Pediatric Oncology Study Group.